2006
DOI: 10.1017/s0950268806006200
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of retail food and human Campylobacter isolates on the island of Ireland from 2001–2002

Abstract: The antimicrobial resistance profiles of Campylobacter isolates recovered from a range of retail food samples (n=374) and humans (n=314) to eight antimicrobial compounds were investigated. High levels of resistance in food C. jejuni isolates were observed for ceftiofur (58%), ampicillin (25%) and nalidixic acid (17%) with lower levels observed for streptomycin (7.9%) and chloramphenicol (8.3%). A total of 80% of human C. jejuni isolates were resistant to ceftiofur, while 17% showed resistance to ampicillin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
4
8
0
Order By: Relevance
“…On the other hand, some EU MSs reported a relatively high level of resistance to erythromycin, e.g., 4% and 18% in Belgium for C. jejuni and C. coli, respectively or 39% of the Campylobacter isolates in the Netherlands (Anonymous 2012b). Furthermore, a relatively low level of resistance of the strains tested to streptomycin (22.8%) obtained during our study is similar to other data where the percentage of such strains was higher among C. coli than C. jejuni (McGill et al 2006;Bardon et al 2011). In the present investigation none of the Campylobacter strains was resistant to another antimicrobial from the aminoglycoside group -gentamicin.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, some EU MSs reported a relatively high level of resistance to erythromycin, e.g., 4% and 18% in Belgium for C. jejuni and C. coli, respectively or 39% of the Campylobacter isolates in the Netherlands (Anonymous 2012b). Furthermore, a relatively low level of resistance of the strains tested to streptomycin (22.8%) obtained during our study is similar to other data where the percentage of such strains was higher among C. coli than C. jejuni (McGill et al 2006;Bardon et al 2011). In the present investigation none of the Campylobacter strains was resistant to another antimicrobial from the aminoglycoside group -gentamicin.…”
Section: Discussionsupporting
confidence: 91%
“…This result agrees with the previous studies which suggested that none of C. jejuni isolates from humans and companion animals was resistant [16,28]. However, other studies reported 3-6.8% of erythromycin resistance in C. jejuni isolated from humans [7,18].…”
Section: Discussionsupporting
confidence: 92%
“…isolates from humans and companion animals [16,18,30]. A higher rate of resistance to tetracycline was also observed, mainly in C. coli isolated from pigs and broilers (62 and 52%, respectively) [30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be pointed out that thermophilic Campylobacter spp. are intrinsically resistant to cephalosporins, including ceftiofur (6,27,42), and these compounds often are included in the selective medium for the isolation of Campylobacter (6). Regardless, we included ceftiofur in this panel, since it is frequently used in food animal production for the treatment of diseases caused by other bacterial pathogens.…”
Section: Mlst Of C Jejuni Isolatesmentioning
confidence: 99%